Pengaruh Media Pembelajaran Articulate Storyline Interaktif Terhadap Kemampuan Menulis Teks Cerpen Siswa Kelas VII SMP N 13 Medan - Bakara, Sondang Loren A.; S, Monalisa Frince; Sitohang, Tigor (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This study aims to determine the effect of using articulate storyline media as a means of delivering material on students' ability to write short story texts. This dilator is caused by students' low writing skills, especially in short story text material. This research uses quantitative experimental methods. The population in this study were all class VII students of SMP N 13 Medan. The data collection technique used is an assignment test which functions to determine students' ability to write short story texts. The results of this research obtained an average of 76.15 for the experimental class and 63.18 for the control class. The data requirements test results show that the data for both classes are normally distributed and homogeneous. in the t test it is obtained that tcount > ttable = (8.9448> 1.6706). Thus it is concluded that there is a significant influence of the use of articulate storyline media on students' ability to write short story texts.